An Antisense Oligonucleotide Leads to Suppressed Transcription of Hdac2 and Long-Term Memory Enhancement - Shane G. Poplawski; Krassimira A. Garbett; Rebekah L. McMahan; Holly B. Kordasiewicz; Hien Zhao; Andrew J. Kennedy; Slavina B. Goleva; Teresa H. Sanders; S. Timothy Motley; Eric E. Swayze; David J. Ecker; J. David Sweatt; et al. (Elsevier, 2020)
Knockout of the memory suppressor gene histone deacetylase 2 (Hdac2) in mice elicits cognitive enhancement, and drugs that block HDAC2 have potential as therapeutics for disorders affecting memory. Currently available HDAC2 catalytic activity inhibitors are not fully isoform specific and have short half-lives. Antisense oligonucleotides (ASOs) are drugs that elicit extremely long-lasting, specific inhibition through base pairing with RNA targets. We utilized an ASO to reduce Hdac2 messenger RNA (mRNA) in mice and determined its longevity, specificity, and mechanism of repression. A single injection of the Hdac2-targeted ASO in the central nervous system produced persistent reduction in HDAC2 protein and Hdac2 mRNA levels for 16 weeks. It enhanced object location memory for 8 weeks. RNA sequencing (RNA-seq) analysis of brain tissues revealed that the repression was specific to Hdac2 relative to related Hdac isoforms, and Hdac2 reduction caused alterations in the expression of genes involved in extracellular signal-regulated kinase (ERK) and memory-associated immune signaling pathways. Hdac2-targeted ASOs also suppress a nonpolyadenylated Hdac2 regulatory RNA and elicit direct transcriptional suppression of the Hdac2 gene through stalling RNA polymerase II. These findings identify transcriptional suppression of the target gene as a novel mechanism of action of ASOs. Keywords: antisense oligonucleotide, Hdac2, memory, autism, Alzheimer's disease, extra-coding RNA, transcription